Safety and Feasibility of Thoracoscopic Lung Resection for Non-Small-Cell Lung Cancer in Octogenarians. Issue 1 (January 2021) - Lou, Xiaoying; Sanders, Andrew; Wagh, Kaustubh; Binongo, Jose N.; Sancheti, Manu; Javidfar, Jeffrey; Pickens, Allan; Fernandez, Felix; Force, Seth; Khullar, Onkar
Objective: Octogenarians comprise an increasing proportion of patients presenting with non-small-cell lung cancer (NSCLC). This study examines postoperative morbidity and mortality, and long-term survival in octogenarians undergoing thoracoscopic anatomic lung resection for NSCLC, compared with younger cohorts. Methods: We conducted a retrospective review of our institutional Society of Thoracic Surgeons General Thoracic Surgery Database of all patients ≥60 years old undergoing elective lobectomy or segmentectomy for pathologic stage I, II, and IIIA NSCLC between 2009 and 2018. Results were compared between octogenarians ( n = 71) to 2 younger cohorts of 60- to 69-year-olds ( n = 359) and 70- to 79-year-olds ( n = 308). Long-term survival among octogenarians was graphically summarized using the Kaplan–Meier method. Cox regression analysis was used to identify preoperative risk factors for mortality. Results: A greater proportion of octogenarians required intensive care unit admission and discharge to extended-care facilities; however, postoperative length of stay was similar between groups. Among postoperative complications, arrhythmia and renal failure were more likely in the older cohort. Compared to the youngest cohort, in-hospital and 30-day mortality were highest among octogenarians. Overall survival among octogenarians at 1, 3, and 5 years was 87.3%, 61.8%, and 50.5%, respectively. On multivariable Cox regression analysis of baseline demographic variables, presence of stroke (hazard ratio [HR] = 28.5, 95% confidence interval [CI]: 6.1 to 132.7, P < 0.001) and coronary artery disease (HR = 2.5, 95% CI: 1.2 to 5.3, P = 0.02) were significant predictors of overall mortality among octogenarians. Conclusions: Thoracoscopic resection can be performed with favorable early postoperative outcomes among octogenarians. Long-term survival, although comparable to their healthy peers, is worse than those of younger cohorts. Further study into preoperative risk stratification and alternative therapies among octogenarians is needed.